L’AVENIR DES PERSONNES VIVANT AVEC LE VIH/SIDA ET LEURS ENFANTS A KISANGANI, EN REPUBLIQUE DEMOCRATIQUE DU CONGO - LIFOLI BALEA, Jean-Pierre; MassabaAwesse, Christian (IJRDO - Journal of Social Science and Humanities Research, 2018)
We intended to study how people living with the VIH/SIDA imagine their future to the look of all difficulties and the fears that the infection of which they are victims represents. We wanted to examine also how they project the future of their children in this environment of multiform crises and disarrays. However, our report seems interesting had consideration to the contradictory results to which us succeeded. The hope seemed to take the over on the discouragement; people living with the VIH/SIDA of Kisangani believe in the best.